Absolute expressions of hypoxia-inducible factor-1 alpha (HIF1A) transcript and the associated genes in chicken skeletal muscle with white striping and wooden breast myopathies - Malila, Yuwares (PLoS One, 2019)
Development of white striping (WS) and wooden breast (WB) in broiler breast meat have been linked to hypoxia, but their etiologies are not fully understood. This study aimed at investigating absolute expression of hypoxia-inducible factor-1 alpha subunit (HIF1A) and genes involved in stress responses and muscle repair using a droplet digital polymerase chain reaction. Total RNA was isolated from pectoralis major collected from male 6-week-old medium (carcass weight ≤ 2.5 kg) and heavy (carcass weight > 2.5 kg) broilers. Samples were classified as “non-defective” (n = 4), “medium-WS” (n = 6), “heavy-WS” (n = 7) and “heavy-WS+WB” (n = 3) based on abnormality scores. The HIF1A transcript was up-regulated in all of the abnormal groups. Transcript abundances of genes encoding 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 4 (PFKFB4), lactate dehydrogenase-A (LDHA), and phosphorylase kinase beta subunit (PHKB) were increased in heavy-WS but decreased in heavy-WS+WB. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was up-regulated in non-defective samples. The muscle-specific mu-2 isoform of glutathione S-transferases (GSTM2) was up-regulated in the abnormal samples, particularly in the heavy groups. The genes encoding myogenic differentiation (MYOD1) and myosin light chain kinase (MYLK) exhibited similar expression pattern, of which medium-WS and heavy-WS significantly increased compared to non-defective whereas expression in heavy-WS+WB was not different from either non-defective or WS-affected group. The greatest and the lowest levels of calpain-3 (CAPN3) and delta-sarcoglycan (SCGD) were observed in heavy-WS and heavy-WS+WB, respectively. Based on micrographs, the abnormal muscles primarily comprised fibers with cross-sectional areas ranging from 2,000 to 3,000 μm(2). Despite induced glycolysis at the transcriptional level, lower stored glycogen in the abnormal muscles corresponded with the reduced lactate and higher pH within their meats. The findings support hypoxia within the abnormal breasts, potentially associated with oversized muscle fibers. Between WS and WB, divergent glucose metabolism, cellular detoxification and myoregeneration at the transcriptional level could be anticipated.